A method for preparing a functional additive for a composite encapsulation film for a main grid-free battery assembly

Through the co-extrusion preparation of homemade functional additives and adhesive resins, the problem of poor water and aging resistance during the lamination process of main gateless battery module packaging film is solved, and the high adhesion and low composite packaging film are achieved The shrinkage rate improves the overall performance of the battery assembly.

CN118388709BActive Publication Date: 2025-02-07SUZHOU YISHENG OPTICAL MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410577008.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-02-07
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The packaging films of existing main gateless battery modules have poor water and aging resistance during lamination, and insufficient adhesion, which can easily lead to welding tape displacement and dummy joints.

Method used

The composite material was prepared by coextruding functional additives and adhesive resins, and was used to prepare composite encapsulation films of the EVA layer and the POE layer. Functional additives contain nano-scale metal oxides and macromolecular chain structures to improve adhesion and corrosion resistance; viscous resins contain epoxy, ester and silane structures to enhance adhesion and water resistance.

Benefits of technology

The excellent adhesive force, aging resistance and low shrinkage of the composite packaging film are achieved, which reduces the displacement and dummy bonding of the welding tape, and improves the overall performance of the battery assembly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The present invention belongs to the field of photovoltaic materials. The present invention relates to a composite encapsulation film for a main grid-free battery assembly, which is prepared by extruding an EVA layer and a POE layer through formula optimization design, extrusion by an extruder, and casting film formation. The EVA layer comprises 100 parts of EVA resin, 0.8-1.2 parts of a cross-linking agent, 1.0-1.5 parts of a co-cross-linking agent, 4.0-6.0 parts of a functional additive, 0.1-0.2 parts of an antioxidant, and 0.3-0.5 parts of a silane coupling agent as raw materials; the POE layer comprises 100 parts of POE resin, 10-15 parts of PP resin, 8-12 parts of a viscous resin, 0.5-1.0 parts of a cross-linking agent, 1.0-1.5 parts of a co-cross-linking agent, 0.05-0.20 parts of an antioxidant, and 0.05-0.15 parts of a light stabilizer as raw materials. The composite film effectively solves the problems that the water resistance and aging resistance of the main grid-free battery assembly encapsulation film in the prior art are relatively poor at the joint, and the bonding force between the film and the battery sheet is relatively weak.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite packaging adhesive film for a main grid-free battery assembly and belongs to the field of photovoltaic materials. Background Art

[0002] Busbarless cells are gaining increasing attention in the photovoltaic field because of their great potential in terms of solar energy conversion efficiency. Such cells are usually composed of multiple layers of semiconductor materials to achieve higher light absorption efficiency and electronic conduction performance. However, in the manufacture and application of busbarless cells, packaging technology has become a crucial challenge. Traditional packaging methods often fail to meet the special requirements of busbarless cells, and the packaging of these cells requires higher process precision to ensure that the optical and electrical properties of the materials are not affected.

[0003] At present, the traditional photovoltaic encapsulation film on the market cannot be applied to the busbarless battery module. It is easy to cause the welding strip to shift during the lamination process, and the welding strip and the battery cell are prone to virtual connection. The support layer of the existing busbarless load-bearing encapsulation integrated film is mainly EVA resin. Due to the high degree of cross-linking, the peeling strength of the battery cell is generally low. At the same time, EVA will produce acetate ions under hot and humid conditions, which will cause a certain corrosion to the welding strip; at the same time, there is a large shrinkage rate, which leads to the common virtual connection of the welding strip; and the use of POE resin as the encapsulation film has the factor of insufficient adhesion of POE material to the battery and glass. In addition, the encapsulation film not only needs a high bonding strength to prevent the welding strip from shifting and virtual connection during the lamination process, but also has good water vapor barrier performance and low corrosion. Therefore, it is necessary to develop a new type of load-bearing encapsulation film for photovoltaic modules to meet the relevant requirements of busbarless battery modules. Summary of the invention

[0004] The purpose of the present invention is to provide a composite encapsulation film for a busbar-free battery assembly and a preparation method thereof, in view of the relatively poor water and aging resistance of the bonding part of the encapsulation film of the busbar-free battery assembly in the prior art, and the relatively weak bonding force between the film and the battery sheet. The present invention prepares a composite material by co-extrusion of a homemade functional additive and a viscous resin, which has excellent viscosity, aging resistance and corrosion resistance, and has broad application potential. The technical solution adopted by the present invention to solve its technical problems is:

[0005] A method for preparing a functional additive comprises the following steps:

[0006] S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I;

[0007] S12, subjecting the vinyl monomer A and the intermediate product I to a polymerization reaction under the action of an initiator A to obtain an intermediate product II;

[0008] S13, placing the nano-sized metal oxide and the silane coupling agent in an alcohol solvent for coupling reaction to obtain an intermediate product III;

[0009] S14, coupling reaction is performed on the intermediate product II and the intermediate product III to obtain the target product.

[0010] Furthermore, the hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; and

[0011] The hydroxyl structure-containing substance and the halogenated olefins are added in a molar ratio of 1:1.

[0012] Furthermore, the hydroxyl-containing substance having a light-stable structure is an o-hydroxybenzophenone and a hindered amine added in a molar ratio of 1.0-3.0:1.0.

[0013] Furthermore, the vinyl monomer A is amino vinyl, hydroxy vinyl, and ester vinyl added in a molar ratio of 4.0-6.0:2.0-4.0:2.0; and

[0014] The aminoolefins are alkenylamines and alkenylamides mixed in a molar ratio of 1.0:2.0-4.0;

[0015] The hydroxy olefins are enols and / or hydroxy acrylates;

[0016] The ester-based olefins are (meth)acrylates and / or non-acrylates.

[0017] Furthermore, the usage ratio of the olefin monomer A and the intermediate product I is 8.0-9.5 mol: 0.5-2.0 mol.

[0018] Furthermore, the usage of the metal oxide, the silane coupling agent and the alcohol solvent is 1g:3.3-5.5g:80mL.

[0019] Furthermore, the usage ratio of the intermediate product II and the intermediate product III is 10g:2.0-3.0g.

[0020] Another object of the present invention is to provide a functional additive prepared by a preparation method.

[0021] A method for preparing a viscous resin comprises the following steps:

[0022] S21, polymerizing the olefin monomer B under the action of initiator B to obtain the target product.

[0023] Furthermore, the vinyl monomer B is epoxy vinyl, ester vinyl, styrene, acrylonitrile, silane vinyl, added in a molar ratio of 4.0-5.0:1.0-2.0:1.0-2.0:1.0-2.0:1.0-2.0:1.0.

[0024] Another object of the present invention is to provide a viscous resin prepared by the preparation method.

[0025] Another object of the present invention is to provide a composite encapsulation film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0026] The EVA layer comprises the following raw materials in parts by weight:

[0027] EVA resin 100 parts;

[0028] Cross-linking agent 0.8-1.2 parts;

[0029] 1.0-1.5 parts of auxiliary cross-linking agent;

[0030] Functional additives 4.0-6.0 parts;

[0031] Antioxidant 0.1-0.2 parts;

[0032] Silane coupling agent 0.3-0.5 parts;

[0033] The POE layer comprises the following raw materials in parts by weight:

[0034] POE resin 100 parts;

[0035] PP resin 10-15 parts;

[0036] 8-12 parts of adhesive resin;

[0037] Cross-linking agent 0.5-1.0 part;

[0038] 1.0-1.5 parts of auxiliary cross-linking agent;

[0039] Antioxidant 0.05-0.20 parts;

[0040] Light stabilizer 0.05-0.15 parts.

[0041] Another object of the present invention is to provide a method for preparing a composite encapsulation film for a busbar-free battery assembly, comprising the following steps:

[0042] S31, mixing, i.e.

[0043] The raw materials of each layer are mixed and configured according to the formula in a mixer to obtain mixed raw materials for standby use;

[0044] S32, co-extrusion, i.e.

[0045] The mixed raw materials in S31 are placed in extruders respectively for melt blending, coextrusion, casting, pulling, stretching, and cooling; and

[0046] S33, film formation, i.e.

[0047] After thickness measurement, edge pressing, shaping, edge cutting and rolling, the composite packaging film for the busbar-free battery assembly is obtained.

[0048] Beneficial effects of the present invention:

[0049] (1) The present invention provides a composite encapsulation film for a busbar-free battery assembly, wherein the EVA layer formula system contains a self-made functional additive and is an organic-inorganic hybrid core-shell structure; the core layer is a nano-scale metal oxide, and the shell layer structure contains a macromolecular chain of silane, amino, amide, hydroxyl, ester, o-hydroxybenzophenone and a hindered amine structure. First, metal oxides are inorganic fillers, which can effectively reduce the shrinkage rate of the film during the lamination process, reduce the displacement and virtual connection of the welding strip, and have excellent adhesion to the substrate; second, nano-scale metal oxides have a large specific surface area, can better adsorb free acid, and have excellent corrosion resistance; third, polar groups such as amide, amino, hydroxyl, and ester groups in the macromolecular chain can further enhance the adhesion of the film on the one hand; on the other hand, they have an inhibitory effect on free acetic acid, further improving the corrosion resistance; fourth, the polar structure of the macromolecule has excellent adsorption for small molecules in the EVA layer, reduces its migration to the interface, and improves the adhesion between EVA and the interface; fifth, the hindered amine and o-hydroxybenzophenone structure in the macromolecular chain, as traditional light stabilizer and ultraviolet absorber components, have excellent antioxidant and anti-aging effects, and hindered amine and o-hydroxybenzophenone have better anti-photooxidation and aging effects at a suitable ratio.

[0050] (2) The present invention provides a composite encapsulation film for a main grid-free battery assembly, wherein the POE layer formula system contains a self-made adhesive resin, which is a macromolecular chain with a side group containing an epoxy group, an ester group, a phenyl group, a cyano group, and a silane structure. First, the chain entanglement of the macromolecule, the main chain structure of the carbon chain, and the phenyl structure ensure that it has a certain compatibility in POE; second, the polar structure of the epoxy group, ester group, and cyano group of the side group, on the one hand, has excellent adhesion to the EVA layer to prevent the composite film from delaminating; on the other hand, it can adsorb polar small molecule additives to prevent them from migrating to the interface to affect the bonding performance and cause delamination; third, the silane structure of the side group focuses on bonding to the substrate; fourth, the adhesive resin in the POE layer has a similar structure to the functional additive shell in the EVA, which can further enhance the bonding strength of the co-extruded surface.

[0051] (3) The present invention provides a composite encapsulation film for a busbar-free battery assembly. The POE layer formula system contains PP resin. On the one hand, the PP resin also has excellent water-blocking properties; on the other hand, the PP resin is easy to crystallize and has a higher melting point, which has a positive effect on improving the service life of the encapsulation film in harsh environments.

[0052] (4) The present invention provides a composite packaging film for a busbar-free battery assembly, which is a co-extruded POE layer and an EVA layer. The low shrinkage property of the POE layer supports the EVA layer, reduces the shrinkage of the EVA layer, and improves the adhesion.

[0053] (5) The present invention provides a method for preparing a composite encapsulation film for a busbar-free battery assembly. Through formula design, the use of small molecule additives is reduced and the adhesion between the layers is improved; at the same time, the method is prepared through a co-extrusion process. Due to the barrier effect of the POE layer, the composite encapsulation film also has excellent anti-PID performance, etc. The product of the present invention is industrialized, has strong operability, and has practical significance. DETAILED DESCRIPTION

[0054] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0055] The purpose of the present invention is to develop a composite encapsulation film for a busbar-free battery assembly to meet the application requirements of existing busbar-free battery assemblies. The idea of ​​implementation is: first, in view of the shortcomings of the existing single-layer film, the EP two-layer composite film is used to solve the problems of water resistance and weather resistance, shrinkage rate and welding strip virtual joint displacement caused by shrinkage rate to a certain extent; then, the respective defects of the EVA layer and the POE layer are targeted, and the solution is designed from the perspective of minimizing the use of small molecule additives. Specifically: on the one hand, the EP composite film is prepared by co-extrusion technology; on the other hand, the functional additives used in the EVA layer and the viscous resin used in the POE layer are prepared respectively, and the water resistance and weather resistance of the EVA layer, the high shrinkage rate and the low adhesion of the POE layer to the substrate are modified respectively. The theoretical basis for the realization is: through molecular structure design, a series of reactions are first carried out, including active hydrogen substitution reaction, double bond free radical polymerization reaction, inorganic silane coupling reaction and coupling substitution reaction to prepare functional additives; the adhesive resin is obtained by double bond free radical polymerization reaction; then the above functional additives are used for EVA layer and the adhesive resin is used for POE layer for co-extrusion preparation, and the composite adhesive film has excellent water and weather resistance, adhesion and low shrinkage and other functions. The embodiments of the present invention are as follows:

[0056] The present invention provides a method for preparing a functional additive, comprising the following steps:

[0057] S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I;

[0058] The hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; and

[0059] The hydroxyl-containing substance having a light-stable structure is o-hydroxybenzophenone and hindered amine added in a molar ratio of 1.0-3.0:1.0.

[0060] S11 includes S111 and / or S112,

[0061] S111, add hydroxyl-containing structure substance A and acid-binding agent A to N,N-dimethylacetamide A, dissolve olefin halides A in N,N-dimethylformamide B and place in a constant pressure dropping funnel, ice bath, stir, and after completion of dropwise addition, control the temperature to continue the reaction at 0-5°C for 8-14 hours. After completion of the reaction, filter, distill under reduced pressure, dissolve the concentrate in dichloromethane A, add saturated sodium bicarbonate solution A to the solution, wash three times, and then wash three times with deionized water A, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate A, filter, distill the filtrate under reduced pressure, and dry it at 80°C in vacuum for 4 hours to obtain the intermediate product IA.

[0062] The dosage ratio of the hydroxyl structure-containing substance A, the acid-binding agent A, the N,N-dimethylformamide A, the halogenated olefin A, the N,N-dimethylformamide B, the dichloromethane A, the saturated sodium bicarbonate solution A, the deionized water A, and the anhydrous sodium sulfate A is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0063] The hydroxyl-containing structure substance A is a substance containing hydroxyl groups and having a light-stable structure;

[0064] The substance containing hydroxyl groups and having a light-stable structure is o-hydroxybenzophenone and / or hindered amine;

[0065] The o-hydroxybenzophenones may be 2,4-dihydroxybenzophenone, 2,2,4,4-tetrahydroxybenzophenone, 2,3,4,4-tetrahydroxybenzophenone, 2,2,4-trihydroxybenzophenone, etc., and 2,4-dihydroxybenzophenone is preferred.

[0066] The hindered amines may be 2,2,6,6-tetramethyl-4-piperidinol, 1,2,2,6,6-pentamethyl-4-piperidinol or 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy, etc., and preferably 2,2,6,6-tetramethyl-4-piperidinol.

[0067] The acid binding agent A can be pyridine, triethylamine, potassium carbonate; and triethylamine is preferred.

[0068] The halogenated olefin A can be oleoyl chloride, palmitoleoyl chloride, undecenoyl chloride, 5-hexenoyl chloride, 4-butenoyl chloride, etc., and undecenoyl chloride is preferred.

[0069] S112, add hydroxyl-containing structural substance B, acid binding agent B and polymerization inhibitor into N,N-dimethylformamide C, dissolve olefin halides B in N,N-dimethylformamide D and place in a constant pressure dropping funnel, raise the temperature to 100-120°C and stir, after the addition is completed, control the temperature and continue the reaction for 1-2 hours, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane B, add saturated sodium bicarbonate solution B to the solution, wash 3 times, then wash 3 times with deionized water B, separate the liquids, take the organic phase, dry with anhydrous sodium sulfate B, filter, distill the filtrate under reduced pressure, and dry at 80°C in vacuum for 4 hours to obtain the intermediate product IB.

[0070] The dosage ratio of the hydroxyl structure substance B, the acid binding agent B, N,N-dimethylformamide C, the halogenated olefin B, N,N-dimethylformamide D, dichloromethane B, the saturated sodium bicarbonate solution B, the deionized water B, and the anhydrous sodium sulfate B is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0071] The hydroxyl-containing structure substance B is a substance containing hydroxyl groups and having a light-stable structure;

[0072] The substance containing hydroxyl groups and having a light-stable structure is o-hydroxybenzophenone;

[0073] The o-hydroxybenzophenones may be 2,4-dihydroxybenzophenone, 2,2,4,4-tetrahydroxybenzophenone, 2,3,4,4-tetrahydroxybenzophenone, 2,2,4-trihydroxybenzophenone, etc., and 2,4-dihydroxybenzophenone is preferred.

[0074] The acid binding agent B can be pyridine, triethylamine, potassium carbonate; and potassium carbonate is preferred.

[0075] The halogenated olefin B may be 4-bromo-1-butene, 5-bromo-1-pentene, 6-bromo-1-hexene, 7-bromo-1-heptene, 8-bromo-1-octene, bromoundecene, etc., and preferably 8-bromo-1-octene.

[0076] The amount of the polymerization inhibitor used is 0.5% of the mass of the halogenated olefin B.

[0077] The polymerization inhibitor may be hydroquinone, p-hydroxyanisole, tert-butylhydroquinone, etc., and tert-butylhydroquinone is preferred.

[0078] S12, add olefin monomer A, intermediate product I and initiator AIBN to N,N-dimethylformamide E, raise the temperature to 75-85°C, and stir for 6-10 hours; after the reaction is completed, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain intermediate product II.

[0079] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 8.0-9.5 mol: 0.5-2.0 mol: 800 mL.

[0080] The olefin monomer A is aminoolefin, hydroxyolefin, and esterolefin, which are added in a molar ratio of 4.0-6.0:2.0-4.0:2.0.

[0081] The aminoolefins are alkenylamines and alkenylamides mixed in a molar ratio of 1.0:2.0-4.0;

[0082] The alkenylamine, wherein the amino structure needs to react with the intermediate product III in the next step, the amino structure is preferably a primary amine structure; the alkenylamine may be allylamine, 2-methylallylamine, etc.; and allylamine is preferred;

[0083] The alkenyl amide has a higher polarity and a higher bonding strength to the substrate due to its amide structure, so a higher ratio is required; the alkenyl amide can be acrylamide, diacetone acrylamide, etc., and diacetone acrylamide is preferred.

[0084] The hydroxy olefins are enols and / or hydroxy acrylates;

[0085] The enol may be 4-penten-1-ol, 5-hexen-1-ol, 8-nonen-1-ol, 9-decen-1-ol, undecenol, etc.; and preferably 8-nonen-1-ol;

[0086] The hydroxy acrylate may be hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 4-hydroxybutyl acrylate, etc., and preferably hydroxyethyl methacrylate.

[0087] The ester-based olefins may be methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, etc.; and ethyl methacrylate is preferred.

[0088] The amount of the initiator AIBN used is 1.0-1.5% of the total mass of the olefin monomer and the intermediate product I.

[0089] S13, adding nano-sized metal oxide and silane coupling agent to an alcohol solvent, ultrasonically oscillating for 0.5 h, standing at room temperature for 2 h, reacting at 40-60° C. for 6-10 h, filtering, taking insoluble matter, and drying at 40° C. for 12 h to obtain an intermediate product III.

[0090] The usage ratio of the nano-scale metal oxide, the silane coupling agent and the alcohol solvent is 1g:3.5-5.5g:80mL.

[0091] The nano-scale metal oxide may be magnesium oxide, aluminum oxide or zinc oxide, etc., and magnesium oxide is preferred;

[0092] The magnesium oxide, with a particle size of 500-1000 nm and model DK-MgO-002, was purchased from Beijing Dekedaojin Technology Co., Ltd.

[0093] The alumina, with an average particle size of 500 nm and model number DK-Al2O3-500, was purchased from Beijing Dekedaojin Technology Co., Ltd.

[0094] The zinc oxide, with an average particle size of 200 nm and model number ZT-J300, was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0095] The silane coupling agent is an acryloxy silane coupling agent or an epoxy silane coupling agent;

[0096] The acryloxysilane coupling agent may be KH570, KH571, KH670, GX572, etc., and preferably GX572.

[0097] The epoxy silane coupling agent may be KH560 or the like; and KH560 is preferred.

[0098] The alcohol solvent may be anhydrous methanol, anhydrous ethanol, anhydrous isopropanol, etc., and anhydrous ethanol is preferred.

[0099] S14, adding intermediate product II and intermediate product III to N,N-dimethylformamide F, heating to 40-60°C and stirring for 3-6 hours, distilling under reduced pressure, and drying in a vacuum oven at 40°C for 12 hours to obtain the target product.

[0100] The usage ratio of the intermediate product II, the intermediate product III and N,N-dimethylformamide F is 10g:2.0-3.0g:400mL.

[0101] A method for preparing a viscous resin comprises the following steps:

[0102] S21, add olefin monomer B and initiator AIBN to N,N-dimethylformamide G, raise the temperature to 75-85°C, and stir for 6-10 hours; after the reaction is completed, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain the target product.

[0103] The olefin monomer B is epoxy olefins, ester olefins, styrene, acrylonitrile, silane olefins, and is added in a molar ratio of 4.0-5.0:1.0-2.0:1.0-2.0:1.0-2.0:1.0-2.0:1.0

[0104] The epoxy olefins may be glycidyl methacrylate, allyl glycidyl ether, 1,2-epoxy-5-hexene, 1,2-epoxy-7-octene or 1,2-epoxy-9-decene, etc., and preferably allyl glycidyl ether.

[0105] The ester-based olefins may be methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isooctyl (meth)acrylate, etc., and isooctyl methacrylate is preferred.

[0106] The silane olefin is vinyl silane or acryloxy silane;

[0107] The vinyl silane may be KH151, KH171 or KH172, etc.;

[0108] The acryloxysilane may be KH570, KH571, KH670 or GX572, etc., and preferably KH570.

[0109] The amount of the initiator AIBN used is 1.0-1.5% of the total mass of the olefin monomers.

[0110] The embodiment of the present invention provides a composite encapsulation film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0111] The EVA layer comprises the following raw materials in parts by weight:

[0112] EVA resin 100 parts;

[0113] Cross-linking agent 0.8-1.2 parts;

[0114] 1.0-1.5 parts of auxiliary cross-linking agent;

[0115] Functional additives 4.0-6.0 parts;

[0116] Antioxidant 0.1-0.2 parts;

[0117] Silane coupling agent 0.3-0.5 parts;

[0118] The POE layer comprises the following raw materials in parts by weight:

[0119] POE resin 100 parts;

[0120] PP resin 10-15 parts;

[0121] 8-12 parts of adhesive resin;

[0122] Cross-linking agent 0.5-1.0 part;

[0123] 1.0-1.5 parts of auxiliary cross-linking agent;

[0124] Antioxidant 0.05-0.20 parts;

[0125] Light stabilizer 0.05-0.15 parts.

[0126] The EVA resin described in the present invention has a VA content of 28-33%. In the following embodiments of the present invention, the EVA resin with a VA content of 33% and a melt index (MI) of 31 is preferably purchased from DuPont Company of the United States.

[0127] The POE resin described in the following examples of the present invention has a model number of XUS38660 and is purchased from The Dow Chemical Company of the United States.

[0128] The PP resin described in the following examples of the present invention is brand 1300 produced by Yanshan Petrochemical Company.

[0129] The crosslinking agent in the present invention can be benzoyl peroxide, 2,5-dimethyl-2,5-bis(benzoyl peroxide)hexane, dicyclohexyl peroxycarbonate or diisopropylbenzene peroxide, etc.; the crosslinking agent in the following embodiments of the present invention is 2,5-dimethyl-2,5-bis(benzoyl peroxide)hexane.

[0130] The auxiliary cross-linking agent in the present invention is allyl and / or acryloxy.

[0131] The allyl cross-linking auxiliary agent may be triallyl cyanurate or triallyl isocyanurate.

[0132] The acryloxy-based co-crosslinking agent may be any combination of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and pentaerythritol triacrylate.

[0133] The auxiliary cross-linking agent described in the following embodiments of the present invention is triallyl isocyanurate, trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate and pentaerythritol triacrylate added in a mass ratio of 8:3:2:2.

[0134] The antioxidant described in the present invention is a combination of hindered phenols and phosphites. The hindered phenol antioxidants may be antioxidant 1010, antioxidant 1076, antioxidant 264, antioxidant 2246, etc.; and antioxidant 1010 is preferred. The phosphite antioxidants may be antioxidant 168, antioxidant 242, antioxidant TPP, etc.; and antioxidant 168 is preferred. In the following embodiments of the present invention, the antioxidants are antioxidant 1010 and antioxidant 168 added in a mass ratio of 1:2.

[0135] The light stabilizer in the present invention is a hindered amine. The hindered amine may be UV-292, UV-770 or GW540, etc., and UV-292 is preferred. The light stabilizer in the following embodiments of the present invention is UV-292.

[0136] The coupling agent described in the following embodiments of the present invention is a silane coupling agent, specifically a vinyl silane coupling agent, which may be KH151 or KH171, etc., and KH171 is preferred.

[0137] In order to better understand the above invention, a method for preparing a composite encapsulation film for a busbar-free battery assembly in the following embodiment of the present invention comprises the following steps:

[0138] S31, mixing, i.e.

[0139] The raw materials of each layer are mixed and configured according to the formula in a mixer respectively, and mixed and stirred at a temperature of 40° C. and a rotation speed of 80 rpm for 2 hours to obtain a mixed raw material for standby use;

[0140] S32, co-extrusion, i.e.

[0141] The POE layer raw material is placed in a twin-screw extruder, and melt blended at a temperature of 90°C, 95°C, 105°C, and 110°C in each zone and a rotation speed of 50 rpm; the EVA layer raw material is placed in a twin-screw extruder, and the temperature of each zone is 80°C, 90°C, 100°C, and 105°C in each zone and a rotation speed of 45 rpm, and the material is discharged through a co-extrusion cast film die, pulled, and stretched; and

[0142] S33, film formation, i.e.

[0143] After thickness measurement, edge pressing, shaping, edge trimming, and rolling, the composite packaging film for busbar-free battery components (total thickness 500 μm, POE layer 200 μm, EVA layer 300 μm) was obtained.

[0144] In order to further understand the present invention, a composite packaging film for a busbar-free battery assembly provided by the present invention is described in detail below in conjunction with specific embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0145] Example 1

[0146] A method for preparing a functional additive comprises the following steps:

[0147] S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I;

[0148] The hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; and

[0149] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 2.0:1.0.

[0150] S11 includes S111 and S112,

[0151] S111, add 2,2,6,6-tetramethyl-4-piperidinol and triethylamine to N,N-dimethylacetamide A, dissolve undecenoyl chloride in N,N-dimethylformamide B and place in a constant pressure dropping funnel, ice bath, stir, and after the addition is completed, control the reaction at 0°C for 10 hours. After the reaction is completed, filter and distill under reduced pressure, dissolve the concentrate in dichloromethane A, add saturated sodium bicarbonate solution A to the solution, wash 3 times, and then wash 3 times with deionized water A, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate A, filter, distill the filtrate under reduced pressure, and dry it at 80°C in vacuum for 4 hours to obtain the intermediate product IA.

[0152] The dosage ratio of the 2,2,6,6-tetramethyl-4-piperidinol, triethylamine, N,N-dimethylformamide A, undecylenoyl chloride, N,N-dimethylformamide B, dichloromethane A, saturated sodium bicarbonate solution A, deionized water A, and anhydrous sodium sulfate A is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g.

[0153] Its infrared data are as follows: 3512cm -1 :-OH does not exist; 3287cm -1 :-NH- (sharp peak) exists; 1735cm -1 :-C=O exists; 1622cm -1 :-C=C- exists; 703cm -1 : C-Cl does not exist.

[0154] S112, add 2,4-dihydroxybenzophenone, potassium carbonate and tert-butylhydroquinone to N,N-dimethylformamide C, dissolve preferably 8-bromo-1-octene in N,N-dimethylformamide D and place in a constant pressure dropping funnel, heat to 110°C and stir, after the addition is completed, control the temperature and continue to react for 1.5 hours, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane B, add saturated sodium bicarbonate solution B to the solution, wash 3 times, then wash 3 times with deionized water B, separate the liquids, take the organic phase, dry with anhydrous sodium sulfate B, filter, distill the filtrate under reduced pressure, and dry in vacuo at 80°C for 4 hours to obtain the intermediate product IB.

[0155] The usage ratio of the 2,4-dihydroxybenzophenone, potassium carbonate, N,N-dimethylformamide C, preferably 8-bromo-1-octene, N,N-dimethylformamide D, dichloromethane B, saturated sodium bicarbonate solution B, deionized water B, and anhydrous sodium sulfate B is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0156] The amount of tert-butylhydroquinone used is preferably 0.5% of the mass of 8-bromo-1-octene.

[0157] Its infrared data are as follows: 3501cm -1 :-OH exists and weakens; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : benzene ring exists; 1621cm -1 :-C=C- exists; 647cm -1 :-C-Br does not exist.

[0158] S12, add olefin monomer A, intermediate product I, and initiator AIBN to N,N-dimethylformamide E, raise the temperature to 80°C, and stir for 8 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain intermediate product II ( PDI = 1.66).

[0159] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 8.5 mol: 1.5 mol: 800 mL.

[0160] The olefin monomer A is aminoolefin, 8-nonen-1-ol, and ethyl methacrylate, which are added in a molar ratio of 5.0:3.0:2.0.

[0161] The aminoolefin is a mixture of allylamine and diacetone acrylamide in a molar ratio of 1.0:3.0;

[0162] The amount of the initiator AIBN used is 1.0% of the total mass of the olefin monomer and the intermediate product I.

[0163] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1622cm -1 、1605cm-1 、810cm -1 :-C=C- does not exist.

[0164] S13, adding nano-magnesium oxide and silane coupling agent GX572 to anhydrous ethanol solvent, ultrasonically oscillating for 0.5 h, standing at room temperature for 2 h, reacting at 40° C. for 10 h, filtering, taking the insoluble matter, and drying at 40° C. for 12 h to obtain an intermediate product III.

[0165] The usage ratio of the nano-magnesium oxide, the silane coupling agent GX572, and the anhydrous ethanol solvent is 1 g:4.5 g:80 mL.

[0166] Its infrared data are as follows: 3440cm -1 :-OH weakened; 1735cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- exists; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0167] S14, adding intermediate product II and intermediate product III to N,N-dimethylformamide F, heating to 40°C and stirring for 6 hours, then distilling under reduced pressure, and drying in a vacuum oven at 40°C for 12 hours to obtain the target product.

[0168] The usage ratio of the intermediate product II, the intermediate product III and N,N-dimethylformamide F is 10 g:2.5 g:400 mL.

[0169] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist and weaken; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- does not exist; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0170] A method for preparing a viscous resin comprises the following steps:

[0171] S21, add olefin monomer B and initiator AIBN to N,N-dimethylformamide G, raise the temperature to 80°C, and stir for 8 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain the target product ( PDI = 1.62).

[0172] The vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570, which are added in a molar ratio of 4.0:1.5:1.5:2.0:1.0.

[0173] The amount of the initiator AIBN used is 1.0% of the total mass of the olefin monomers.

[0174] Its infrared data are as follows: 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 2258cm -1 :Cyanide exists; 1735cm -1 :-C=O exists; 1218cm -1 、911cm -1 、835cm -1 : Epoxy group exists; 1109cm -1 、801cm -1 :-Si-O- exists; 1622cm -1 、1605cm -1 、810cm -1 :-C=C- does not exist.

[0175] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0176] The EVA layer comprises the following raw materials in parts by weight:

[0177] EVA resin 100 parts;

[0178] 1.0 part of cross-linking agent;

[0179] 1.2 parts of auxiliary cross-linking agent;

[0180] Functional additives 5.0 parts;

[0181] 0.15 parts of antioxidant;

[0182] Silane coupling agent KH171 0.4 parts;

[0183] The POE layer comprises the following raw materials in parts by weight:

[0184] POE resin 100 parts;

[0185] PP resin 13 parts;

[0186] 10 parts of adhesive resin;

[0187] 0.8 part of cross-linking agent;

[0188] 1.2 parts of auxiliary cross-linking agent;

[0189] Antioxidant 0.14 parts;

[0190] Light stabilizer 0.10 parts

[0191] Example 2

[0192] The rest is the same as in Example 1, except that:

[0193] A method for preparing a functional additive comprises the following steps:

[0194] S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I;

[0195] The hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; and

[0196] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 2.0:1.0.

[0197] S11 includes S111 and S112,

[0198] S111, add 2,2,6,6-tetramethyl-4-piperidinol and triethylamine to N,N-dimethylacetamide A, dissolve undecenoyl chloride in N,N-dimethylformamide B and place in a constant pressure dropping funnel, ice bath, stir, after the addition is completed, control the reaction at 5°C for 8 hours, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane A, add saturated sodium bicarbonate solution A to the solution, wash 3 times, then wash 3 times with deionized water A, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate A, filter, distill the filtrate under reduced pressure, and dry it at 80°C in vacuum for 4 hours to obtain the intermediate product IA.

[0199] The dosage ratio of the 2,2,6,6-tetramethyl-4-piperidinol, triethylamine, N,N-dimethylformamide A, undecylenoyl chloride, N,N-dimethylformamide B, dichloromethane A, saturated sodium bicarbonate solution A, deionized water A, and anhydrous sodium sulfate A is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g.

[0200] Its infrared data are as follows: 3512cm -1:-OH does not exist; 3287cm -1 :-NH- (sharp peak) exists; 1735cm -1 :-C=O exists; 1622cm -1 :-C=C- exists; 703cm -1 : C-Cl does not exist.

[0201] S112, add 2,4-dihydroxybenzophenone, potassium carbonate and tert-butylhydroquinone to N,N-dimethylformamide C, dissolve preferably 8-bromo-1-octene in N,N-dimethylformamide D and place in a constant pressure dropping funnel, heat to 120°C and stir, after the addition is completed, control the temperature and continue the reaction for 1 hour, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane B, add saturated sodium bicarbonate solution B to the solution, wash 3 times, then wash 3 times with deionized water B, separate the liquids, take the organic phase, dry with anhydrous sodium sulfate B, filter, distill the filtrate under reduced pressure, and dry in vacuo at 80°C for 4 hours to obtain the intermediate product IB.

[0202] The usage ratio of the 2,4-dihydroxybenzophenone, potassium carbonate, N,N-dimethylformamide C, preferably 8-bromo-1-octene, N,N-dimethylformamide D, dichloromethane B, saturated sodium bicarbonate solution B, deionized water B, and anhydrous sodium sulfate B is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0203] The amount of tert-butylhydroquinone used is preferably 0.5% of the mass of 8-bromo-1-octene.

[0204] Its infrared data are as follows: 3501cm -1 :-OH exists and weakens; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : benzene ring exists; 1621cm -1 :-C=C- exists; 647cm -1 :-C-Br does not exist.

[0205] S12, add olefin monomer A, intermediate product I, and initiator AIBN to N,N-dimethylformamide E, raise the temperature to 75°C, and stir for 10 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain intermediate product II ( PDI = 1.64).

[0206] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 8.5 mol: 1.5 mol: 800 mL.

[0207] The vinyl monomer A is amino vinyl, hydroxyethyl methacrylate and ethyl methacrylate, which are added in a molar ratio of 5.0:3.0:2.0.

[0208] The aminoolefin is a mixture of allylamine and diacetone acrylamide in a molar ratio of 1.0:3.0;

[0209] The amount of the initiator AIBN used is 1.5% of the total mass of the olefin monomer and the intermediate product I.

[0210] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1622cm -1 、1605cm -1 、810cm -1 :-C=C- does not exist.

[0211] S13, adding nano-magnesium oxide and silane coupling agent GX572 to anhydrous ethanol solvent, ultrasonically oscillating for 0.5 h, standing at room temperature for 2 h, reacting at 60° C. for 6 h, filtering, taking the insoluble matter, and drying at 40° C. for 12 h to obtain intermediate product III.

[0212] The usage ratio of the nano-magnesium oxide, the silane coupling agent GX572, and the anhydrous ethanol solvent is 1 g:4.5 g:80 mL.

[0213] Its infrared data are as follows: 3440cm -1 :-OH weakened; 1735cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- exists; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0214] S14, adding intermediate product II and intermediate product III to N,N-dimethylformamide F, heating to 60°C and stirring for 3 hours, then distilling under reduced pressure, and drying in a vacuum oven at 40°C for 12 hours to obtain the target product.

[0215] The usage ratio of the intermediate product II, the intermediate product III and N,N-dimethylformamide F is 10g:2.0g:400mL.

[0216] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist and weaken; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- does not exist; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0217] A method for preparing a viscous resin comprises the following steps:

[0218] S21, add olefin monomer B and initiator AIBN to N,N-dimethylformamide G, raise the temperature to 75°C, and stir for 10 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain the target product ( PDI = 1.62).

[0219] The vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570, which are added in a molar ratio of 5.0:2.0:1.0:1.0:1.0.

[0220] The amount of the initiator AIBN used is 1.5% of the total mass of the olefin monomers.

[0221] Its infrared data are as follows: 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 2258cm -1 :Cyanide exists; 1735cm -1 :-C=O exists; 1218cm -1 、911cm -1 、835cm -1 : Epoxy group exists; 1109cm -1 、801cm -1 :-Si-O- exists; 1622cm -1 、1605cm -1 、810cm -1 :-C=C- does not exist.

[0222] Example 3

[0223] The rest is the same as in Example 1, except that:

[0224] A method for preparing a functional additive comprises the following steps:

[0225] S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I;

[0226] The hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; and

[0227] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 2.0:1.0.

[0228] S11 includes S111 and S112,

[0229] S111, add 2,2,6,6-tetramethyl-4-piperidinol and triethylamine to N,N-dimethylacetamide A, dissolve undecenoyl chloride in N,N-dimethylformamide B and place in a constant pressure dropping funnel, ice bath, stir, and after the addition is completed, control the reaction at 0°C for 14 hours. After the reaction is completed, filter and distill under reduced pressure, dissolve the concentrate in dichloromethane A, add saturated sodium bicarbonate solution A to the solution, wash three times, and then wash three times with deionized water A, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate A, filter, distill the filtrate under reduced pressure, and dry it at 80°C in vacuum for 4 hours to obtain the intermediate product IA.

[0230] The dosage ratio of the 2,2,6,6-tetramethyl-4-piperidinol, triethylamine, N,N-dimethylformamide A, undecylenoyl chloride, N,N-dimethylformamide B, dichloromethane A, saturated sodium bicarbonate solution A, deionized water A, and anhydrous sodium sulfate A is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g.

[0231] Its infrared data are as follows: 3512cm -1 :-OH does not exist; 3287cm -1 :-NH- (sharp peak) exists; 1735cm -1 :-C=O exists; 1622cm -1 :-C=C- exists; 703cm -1 : C-Cl does not exist.

[0232] S112, add 2,4-dihydroxybenzophenone, potassium carbonate and tert-butylhydroquinone to N,N-dimethylformamide C, dissolve preferably 8-bromo-1-octene in N,N-dimethylformamide D and place in a constant pressure dropping funnel, heat to 100°C and stir, after the addition is completed, control the temperature and continue to react for 2 hours, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane B, add saturated sodium bicarbonate solution B to the solution, wash 3 times, then wash 3 times with deionized water B, separate the liquids, take the organic phase, dry with anhydrous sodium sulfate B, filter, distill the filtrate under reduced pressure, and dry in vacuo at 80°C for 4 hours to obtain the intermediate product IB.

[0233] The usage ratio of the 2,4-dihydroxybenzophenone, potassium carbonate, N,N-dimethylformamide C, preferably 8-bromo-1-octene, N,N-dimethylformamide D, dichloromethane B, saturated sodium bicarbonate solution B, deionized water B, and anhydrous sodium sulfate B is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0234] The amount of tert-butylhydroquinone used is preferably 0.5% of the mass of 8-bromo-1-octene.

[0235] Its infrared data are as follows: 3501cm -1 :-OH exists and weakens; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : benzene ring exists; 1621cm -1 :-C=C- exists; 647cm -1 :-C-Br does not exist.

[0236] S12, add olefin monomer A, intermediate product I, and initiator AIBN to N,N-dimethylformamide E, raise the temperature to 85°C, and stir for 6 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain intermediate product II ( PDI = 1.67).

[0237] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 8.5 mol: 1.5 mol: 800 mL.

[0238] The vinyl monomer A is amino vinyl, hydroxy vinyl, and ethyl methacrylate, which are added in a molar ratio of 5.0:3.0:2.0.

[0239] The aminoolefin is a mixture of allylamine and diacetone acrylamide in a molar ratio of 1.0:3.0;

[0240] The hydroxy olefin is a mixture of 8-nonen-1-ol and hydroxyethyl methacrylate in a molar ratio of 1.0:1.0;

[0241] The amount of the initiator AIBN used is 1.0% of the total mass of the olefin monomer and the intermediate product I.

[0242] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1622cm -1 、1605cm -1 、810cm -1 :-C=C- does not exist.

[0243] S13, adding nano-magnesium oxide and silane coupling agent GX572 to anhydrous ethanol solvent, ultrasonically oscillating for 0.5 h, standing at room temperature for 2 h, reacting at 50° C. for 8 h, filtering, taking the insoluble matter, and drying at 40° C. for 12 h to obtain an intermediate product III.

[0244] The usage ratio of the nano-magnesium oxide, the silane coupling agent GX572, and the anhydrous ethanol solvent is 1 g:4.5 g:80 mL.

[0245] Its infrared data are as follows: 3440cm -1 :-OH weakened; 1735cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- exists; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0246] S14, adding intermediate product II and intermediate product III to N,N-dimethylformamide F, heating to 50°C and stirring for 4 hours, then distilling under reduced pressure, and drying in a vacuum oven at 40°C for 12 hours to obtain the target product.

[0247] The usage ratio of the intermediate product II, the intermediate product III and N,N-dimethylformamide F is 10g:3.0g:400mL.

[0248] Its infrared data are as follows: 3250-3550cm -1 :-OH, -NH- exist and weaken; 3013cm -1: benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 1650-1750cm -1 :-C=O exists; 1605cm -1 、811cm -1 :-C=C- does not exist; 1109cm -1 、801cm -1 :-Si-O- exists; 621cm -1 :Mg-O- exists.

[0249] A method for preparing a viscous resin comprises the following steps:

[0250] S21, add olefin monomer B and initiator AIBN to N,N-dimethylformamide G, raise the temperature to 85°C, and stir for 6 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, and vacuum dry at 60°C for 6 hours to obtain the target product ( PDI = 1.62).

[0251] The vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570, which are added in a molar ratio of 4.0:1.0:2.0:2.0:1.0.

[0252] The amount of the initiator AIBN used is 1.0% of the total mass of the olefin monomers.

[0253] Its infrared data are as follows: 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : Benzene ring exists; 2258cm -1 :Cyanide exists; 1735cm -1 :-C=O exists; 1218cm -1 、911cm -1 、835cm -1 : Epoxy group exists; 1109cm -1 、801cm -1 :-Si-O- exists; 1622cm -1 、1605cm -1 、810cm -1 :-C=C- does not exist.

[0254] Example 4

[0255] The rest is the same as in Example 1, except that:

[0256] A method for preparing a functional additive, in step S11,

[0257] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 1.0:1.0.

[0258] Example 5

[0259] The rest is the same as in Example 1, except that:

[0260] A method for preparing a functional additive, in step S11,

[0261] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 3.0:1.0.

[0262] Example 6

[0263] The rest is the same as in Example 1, except that:

[0264] A method for preparing a functional additive, wherein the step S11 is:

[0265] S11 is specifically S111,

[0266] S111, add hydroxyl structure substance A and triethylamine to N,N-dimethylacetamide A, dissolve undecenoyl chloride in N,N-dimethylformamide B and place in a constant pressure dropping funnel, ice bath, stir, after the addition is completed, control the reaction at 0°C for 10 hours, after the reaction is completed; filter, distill under reduced pressure, dissolve the concentrate in dichloromethane A, add saturated sodium bicarbonate solution A to the solution, wash 3 times, then wash 3 times with deionized water A, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate A, filter, distill the filtrate under reduced pressure, and dry it at 80°C in vacuum for 4 hours to obtain the intermediate product IA.

[0267] The dosage ratio of the hydroxyl structure substance A, triethylamine, N,N-dimethylformamide A, undecylenyl chloride, N,N-dimethylformamide B, dichloromethane A, saturated sodium bicarbonate solution A, deionized water A, and anhydrous sodium sulfate A is: 1 mol: 1.0 mol: 400 mL: 1 mol: 150 mL: 500 mL: 400 mL: 400 mL: 50 g;

[0268] The hydroxyl-containing structural substance A is a substance containing hydroxyl groups and having a light-stable structure; and

[0269] The hydroxyl-containing substance having a light-stable structure is 2,4-dihydroxybenzophenone and 2,2,6,6-tetramethyl-4-piperidinol, which are added in a molar ratio of 2.0:1.0.

[0270] Its infrared data are as follows: 3501cm-1 :-OH exists and weakens; 3287cm -1 : -NH- (sharp peak) exists; 3013cm -1 : benzene ring -CH exists; 1495cm -1 、1597cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1622cm -1 :-C=C- exists; 703cm -1 : C-Cl does not exist.

[0271] Example 7

[0272] The rest is the same as in Example 1, except that:

[0273] A method for preparing a functional additive, in step S12,

[0274] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 8.0 mol: 2.0 mol: 800 mL.

[0275] Example 8

[0276] The rest is the same as in Example 1, except that:

[0277] A method for preparing a functional additive, in step S12,

[0278] The usage ratio of the olefin monomer A, the intermediate product I, and N,N-dimethylformamide E is 9.5 mol: 0.5 mol: 800 mL.

[0279] Example 9

[0280] The rest is the same as in Example 1, except that:

[0281] A method for preparing a functional additive, in step S12,

[0282] The olefin monomer A is aminoolefin, 8-nonen-1-ol, and ethyl methacrylate, which are added in a molar ratio of 6.0:2.0:2.0.

[0283] Example 10

[0284] The rest is the same as in Example 1, except that:

[0285] A method for preparing a functional additive, in step S12,

[0286] The olefin monomer A is aminoolefin, 8-nonen-1-ol, and ethyl methacrylate, which are added in a molar ratio of 4.0:4.0:2.0.

[0287] Embodiment 11

[0288] The rest is the same as in Example 1, except that:

[0289] A method for preparing a functional additive, in step S12,

[0290] The aminoolefins are allylamine and diacetone acrylamide mixed in a molar ratio of 1.0:2.0.

[0291] Example 12

[0292] The rest is the same as in Example 1, except that:

[0293] A method for preparing a functional additive, in step S12,

[0294] The aminoolefins are allylamine and diacetone acrylamide mixed in a molar ratio of 1.0:4.0.

[0295] Embodiment 13

[0296] The rest is the same as in Example 1, except that:

[0297] A method for preparing a functional additive, in step S13,

[0298] The usage ratio of the nano-magnesium oxide, the silane coupling agent GX572, and the anhydrous ethanol solvent is 1 g:3.5 g:80 mL.

[0299] Embodiment 14

[0300] The rest is the same as in Example 1, except that:

[0301] A method for preparing a functional additive, in step S13,

[0302] The usage ratio of the nano-magnesium oxide, the silane coupling agent GX572, and the anhydrous ethanol solvent is 1 g:5.5 g:80 mL.

[0303] Embodiment 15

[0304] The rest is the same as in Example 1, except that:

[0305] A method for preparing a functional additive, in step S13,

[0306] The silane coupling agent GX572 was replaced with the silane coupling agent KH560.

[0307] Example 16

[0308] The rest is the same as in Example 1, except that:

[0309] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0310] The EVA layer comprises the following raw materials in parts by weight:

[0311] EVA resin 100 parts;

[0312] 0.8 part of cross-linking agent;

[0313] 1.5 parts of auxiliary cross-linking agent;

[0314] 4.0 parts of functional additives;

[0315] 0.2 parts of antioxidant;

[0316] Silane coupling agent KH171 0.3 parts;

[0317] The POE layer comprises the following raw materials in parts by weight:

[0318] POE resin 100 parts;

[0319] PP resin 15 parts;

[0320] 12 parts of adhesive resin;

[0321] 0.5 part of cross-linking agent;

[0322] 1.5 parts of auxiliary cross-linking agent;

[0323] 0.2 parts of antioxidant;

[0324] Light stabilizer 0.15 parts

[0325] Embodiment 17

[0326] The rest is the same as in Example 1, except that:

[0327] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0328] The EVA layer comprises the following raw materials in parts by weight:

[0329] EVA resin 100 parts;

[0330] 1.2 parts of cross-linking agent;

[0331] 1.0 part of auxiliary cross-linking agent;

[0332] Functional additives 6.0 parts;

[0333] Antioxidant 0.1 part;

[0334] Silane coupling agent KH171 0.5 parts;

[0335] The POE layer comprises the following raw materials in parts by weight:

[0336] POE resin 100 parts;

[0337] PP resin 10 parts;

[0338] 8 parts of adhesive resin;

[0339] 1.0 part of cross-linking agent;

[0340] 1.0 part of auxiliary cross-linking agent;

[0341] Antioxidant 0.05 parts;

[0342] Light stabilizer 0.05 parts.

[0343] Embodiment 18

[0344] The rest is the same as in Example 1, except that:

[0345] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0346] The EVA layer comprises the following raw materials in parts by weight:

[0347] EVA resin 100 parts;

[0348] 1.0 part of cross-linking agent;

[0349] 1.2 parts of auxiliary cross-linking agent;

[0350] 4.0 parts of functional additives;

[0351] 0.15 parts of antioxidant;

[0352] Silane coupling agent KH171 0.4 parts;

[0353] The POE layer comprises the following raw materials in parts by weight:

[0354] POE resin 100 parts;

[0355] PP resin 13 parts;

[0356] 12 parts of adhesive resin;

[0357] 0.8 part of cross-linking agent;

[0358] 1.2 parts of auxiliary cross-linking agent;

[0359] Antioxidant 0.14 parts;

[0360] Light stabilizer 0.10 parts

[0361] Embodiment 19

[0362] The rest is the same as in Example 1, except that:

[0363] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0364] The EVA layer comprises the following raw materials in parts by weight:

[0365] EVA resin 100 parts;

[0366] 1.0 part of cross-linking agent;

[0367] 1.2 parts of auxiliary cross-linking agent;

[0368] Functional additives 6.0 parts;

[0369] 0.15 parts of antioxidant;

[0370] Silane coupling agent KH171 0.4 parts;

[0371] The POE layer comprises the following raw materials in parts by weight:

[0372] POE resin 100 parts;

[0373] PP resin 13 parts;

[0374] 8 parts of adhesive resin;

[0375] 0.8 part of cross-linking agent;

[0376] 1.2 parts of auxiliary cross-linking agent;

[0377] Antioxidant 0.14 parts;

[0378] Light stabilizer 0.10 parts

[0379] The following comparative examples of a composite encapsulation film for a busbar-free battery assembly are compared with Example 1:

[0380] Comparative Example 1

[0381] The rest is the same as in Example 1, except that:

[0382] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0383] No functional additives are added to the EVA layer raw materials; and

[0384] No adhesive resin is added to the POE layer raw material.

[0385] Comparative Example 2

[0386] The rest is the same as in Example 1, except that:

[0387] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0388] No functional additives are added to the EVA layer raw materials.

[0389] Comparative Example 3

[0390] The rest is the same as in Example 1, except that:

[0391] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0392] No adhesive resin is added to the POE layer raw material.

[0393] Comparative Example 4

[0394] The rest is the same as in Example 1, except that:

[0395] In a method for preparing a functional additive, an intermediate product I is not prepared or added.

[0396] Comparative Example 5

[0397] The rest is the same as in Example 1, except that:

[0398] In a method for preparing a functional additive, the substance containing a hydroxyl group and having a light-stable structure in S11 is 2,4-dihydroxybenzophenone.

[0399] Comparative Example 6

[0400] The rest is the same as in Example 1, except that:

[0401] In a method for preparing a functional additive, the substance containing a hydroxyl group and having a light-stable structure in S11 is 2,2,6,6-tetramethyl-4-piperidinol.

[0402] Comparative Example 7

[0403] The rest is the same as in Example 1, except that:

[0404] A method for preparing a functional additive, wherein the olefin monomer A in S12 is aminoolefin and styrene is added in a molar ratio of 5.0:5.0.

[0405] Comparative Example 8

[0406] The rest is the same as in Example 1, except that:

[0407] The functional auxiliary agent is the same as the intermediate product II in Example 1.

[0408] Comparative Example 9

[0409] The rest is the same as in Example 1, except that:

[0410] A method for preparing a functional additive, wherein the magnesium oxide is replaced by silicon dioxide.

[0411] Comparative Example 10

[0412] The rest is the same as in Example 1, except that:

[0413] In a method for preparing a viscous resin, the vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570 added in a molar ratio of 0:1.5:1.5:2.0:1.0, that is, allyl glycidyl ether is not added.

[0414] Comparative Example 11

[0415] The rest is the same as in Example 1, except that:

[0416] In a method for preparing a viscous resin, the vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570 added in a molar ratio of 4.0:1.5:1.5:0:1.0, that is, no acrylonitrile is added.

[0417] Comparative Example 12

[0418] The rest is the same as in Example 1, except that:

[0419] In a method for preparing a viscous resin, the vinyl monomer B is allyl glycidyl ether, isooctyl methacrylate, styrene, acrylonitrile, and KH570 added in a molar ratio of 4.0:1.5:1.5:2.0:0, that is, no KH570 is added.

[0420] Comparative Example 13

[0421] The rest is the same as in Example 1, except that:

[0422] A composite packaging film for a busbar-free battery assembly, comprising an EVA layer and a POE layer.

[0423] No PP resin is added to the POE layer raw material.

[0424] Comparative Example 14

[0425] The rest is the same as in Example 1, except that:

[0426] The invention discloses a packaging adhesive film for a main grid-free battery assembly, which is an EVA adhesive film.

[0427] Comparative Example 15

[0428] The rest is the same as in Example 1, except that:

[0429] A packaging film for a main-grid-free battery assembly is a POE film.

[0430] The physical properties of the films prepared in Examples 1-19 of the present invention and Comparative Examples 1-15 were measured respectively, and the results are shown in Table 1.

[0431] Table 1 Physical test performance of each embodiment

[0432]

[0433]

[0434] First, it can be concluded from Examples 1-19 in Table 1 that the composite encapsulation film for busbar-free battery modules of the present invention has excellent adhesion, aging resistance, water vapor barrier properties, and low shrinkage (EL shows no cold solder joints or displacement after lamination).

[0435] Second, it can be observed from Example 1 and Comparative Examples 1-3 that the composite encapsulation film of the present invention uses a homemade functional additive and a homemade viscous resin, which has an important influence on adhesion, aging resistance and low shrinkage. It can be observed from Example 1 and Comparative Examples 4-6 that the composite encapsulation film of the present invention uses a homemade functional additive, which has excellent aging resistance, and the o-hydroxybenzophenone structure and the hindered amine structure are more effective under a suitable ratio. It can be observed from Example 1 and Comparative Example 7 that the hydroxyl and ester structures in the homemade functional additives help promote their dispersion in EVA and inhibit EVA hydrolysis and reduce oxidative corrosion. It can be observed from Example 1 and Comparative Examples 8-9 that inorganic substances are conducive to reducing shrinkage, and metal oxides have better resistance to acidic gas corrosion. It can be observed from Examples 10-12 that the homemade viscous resin epoxy and cyano groups have greater adhesion to EVA, while the silane coupling agent has greater adhesion to the battery cell. It can be observed from Examples 13-15 that PP resin has a higher melting point and better support for hot pressing of the POE layer and even the composite film at the same temperature; using a single EVA layer has poor water resistance and a high shrinkage rate, resulting in cold solder joints and displacement; using a single POE layer has a problem of poor adhesion.

[0436] In summary, the composite packaging film for the busbar-free battery assembly of the present invention is a composite of an EVA layer and a POE layer, the EVA layer provides adhesion, and the POE layer provides water resistance, weather resistance and low shrinkage; and the homemade functional additives work synergistically with the viscous resin to effectively improve the comprehensive performance of the composite material.

[0437] The test method is as follows:

[0438] (1) Peel force: The battery cell, composite encapsulation film (POE layer and battery cell, EVA layer and glass sheet) and glass sheet are stacked in sequence, hot-pressed and laminated at 145°C, and then tested with reference to the test method provided in GB / T 29848-2018; the components are placed under the following conditions: Test conditions: +85°C, relative humidity 85%, DH 2000h, and then the above operation is repeated for testing.

[0439] (2) EL (electroluminescence) test after lamination: Refer to the test method provided by IEC 61215 to test whether there is cold solder joint or displacement after lamination (POE layer and battery cell are bonded, EVA layer and glass sheet are bonded).

[0440] (3) Module lamination appearance: The composite encapsulation film, busbar-free cell array, and composite encapsulation film are stacked in sequence to obtain a photovoltaic module. The module is then vacuumed for 5 minutes at 145°C and laminated for 10 minutes. The appearance of the cell module obtained after lamination is observed to check whether there are any hidden cracks in the cell or any white spots of delamination.

[0441] (4) Water vapor transmission rate: The test was conducted using a C390H water vapor transmission rate tester in accordance with standard GB / T 21529-2008. The water vapor transmission rate was determined using an infrared sensor method. The test conditions were 38° C. and 90% relative humidity.

[0442] (5) UV aging resistance: The obtained composite encapsulation film was subjected to UV irradiation aging test according to the requirements of the International Electrotechnical Commission standard IEC61345. Test conditions: the surface temperature of the test piece is 60±5℃, the UV wavelength range is 280-400nm, and the irradiation intensity is 15kW·h / m 2 , the UV irradiation test time is 2000hr.

[0443] The visible light transmittance before and after the test was measured, and the visible light transmittance retention rate was calculated according to the following formula:

[0444] Retention rate of visible light transmittance=average light transmittance after the test / average light transmittance before the test×100%.

[0445] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a functional additive, characterized in that: The following steps are involved: S11, subjecting the hydroxyl-containing structure substance to a substitution reaction with a haloolefin to obtain an intermediate product I; S12, subjecting the vinyl monomer A and the intermediate product I to a polymerization reaction under the action of an initiator A to obtain an intermediate product II; S13, placing the nano-sized metal oxide and the silane coupling agent in an alcohol solvent for coupling reaction to obtain an intermediate product III; S14, coupling reaction of intermediate product II and intermediate product III to obtain a target product; The hydroxyl structure-containing substance is a substance containing hydroxyl groups and having a light-stable structure; The substance containing hydroxyl groups and having a light-stable structure is selected from at least one of o-hydroxybenzophenones and hindered amines; The olefin monomer A is selected from at least one of aminoolefins, hydroxyolefins, and esterolefins; The usage ratio of the olefin monomer A and the intermediate product I is 8.0-9.5 mol: 0.5-2.0 mol; The usage ratio of the intermediate product II and the intermediate product III is 10g:2.0-3.0g.

2. The preparation method according to claim 1, characterized in that: The hydroxyl structure-containing substance and the halogenated olefins are added in a molar ratio of 1:

1.

3. The preparation method according to claim 2, characterized in that: The hydroxyl-containing substance having a light-stable structure is o-hydroxybenzophenone and hindered amine added in a molar ratio of 1.0-3.0:1.

0.

4. The preparation method according to claim 1, characterized in that: The vinyl monomer A is amino vinyl, hydroxy vinyl, and ester vinyl added in a molar ratio of 4.0-6.0:2.0-4.0:2.0-4.0; and The aminoolefins are alkenylamines and alkenylamides mixed in a molar ratio of 1.0:2.0-4.

0.

5. The preparation method according to claim 1, characterized in that: The usage of the metal oxide, the silane coupling agent and the alcohol solvent is 1g: 3.3-5.5g: 80mL.

6. A functional additive prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Acrylic pressure-sensitive adhesive composition, method for producing pressure-sensitive adhesive tape using the same, and pressure-sensitive adhesive tape

    JP2011046961A